Comparison of the effectiveness of pregnancy diagnosis in Aceh cattle through measurement of interferon-tau and progesterone concentrations - Budianto Panjaitan; TONGKU NIZWAN SIREGAR; HAFIZUDDIN HAFIZUDDIN; ARMAN SAYUTI; MULYADI ADAM; TEUKU ARMANSYAH; SYAFRUDDIN SYAFRUDDIN (Biodiversitas Journal of Biological Diversity, 2021)
This study aims to determine the effectiveness of IFN-? and progesterone measurement as the basis for pregnancy diagnosis in Aceh cows. The study used twelve cows aged 3-5 years, weighing 150-250 kg, clinically healthy and having normal reproduction. The estrous cycle was synchronized using prostaglandin hormone (LutalyseTM, Pharmacia & Upjohn Company, Pfizer Inc., 25 mg/cow, i.m.) with multiple injection protocol (10-day interval). Heat detection was conducted in the morning (08.00 Western Indonesia Time) and evening (16.00 Western Indonesia Time). Cows were inseminated 12-18 hours after standing heat. Blood was collected on day 4, 5, 6, 7, 14, 15, 16, 17, and 18 post-insemination. Concentrations of IFN-? and progesterone were determined by the ELISA method. Cows with an interferon concentration >6 pg/mL and a progesterone concentration >2 ng/mL were considered pregnant. Pregnancy data were then compared with transrectal ultrasound at day 25 as the gold standard. Concentrations of IFN-? in pregnant and non-pregnant cows were significantly different on day 18 post-insemination, while progesterone concentration was significantly different on day 15. The accuracy of IFN-? pregnancy diagnosis at peak IFN-? expression was obtained on day 18 post-insemination, with an accuracy rate of 66.7%, a sensitivity rate of 60% and a specificity rate of 71.4%. Meanwhile, the accuracy of progesterone-based pregnancy diagnosis was obtained on day 17 post-insemination, with an accuracy rate of 91.6%, a sensitivity rate of 83.3% and a specificity rate of 100%. It was concluded that the diagnosis of pregnancy using progesterone measurement was more effective than IFN-? measurement.